Emerging trends in smart nanocontainers for corrosion applications - Galvão, Tiago L. P. (2022)
In the last decade, the state of the art in corrosion science was defined by the incorporation of smart nanocontainers into coatings for the protection of metallic alloys. These smart materials take advantage of their capacity to store active compounds and release them upon an external trigger associated with corrosion processes. Corrosion inhibitors have been used as active compounds, giving coatings a self-healing capacity once corrosion ensues. In this chapter, it will be described how the concept of smart macromolecular containers is rendering new trends in corrosion science based on: 1) early corrosion detection by the controlled release of color or luminescent sensors; 2) smart nanostructured films grown on top of metallic alloys that are able to enhance corrosion protection by releasing corrosion inhibitors near the surface; and 3) the role of computational approaches in the understanding and subsequent design of nanocontainers and appropriate active substances. At the same time, these trends open the possibility of new applications and opportunities which will also be described.